Air‐Stable 2D Cr5Te8 Nanosheets with Thickness‐Tunable Ferromagnetism. Issue 2 (12th November 2021) - Chen, Chao; Chen, Xiaodie; Wu, Changwei; Wang, Xiao; Ping, Yue; Wei, Xin; Zhou, Xing; Lu, Jiangbo; Zhu, Lujun; Zhou, Jiadong; Zhai, Tianyou; Han, Junbo; et al.
Abstract: 2D magnetic materials have aroused widespread research interest owing to their promising application in spintronic devices. However, exploring new kinds of 2D magnetic materials with better stability and realizing their batch synthesis remain challenging. Herein, the synthesis of air‐stable 2D Cr5 Te8 ultrathin crystals with tunable thickness via tube‐in‐tube chemical vapor deposition (CVD) growth technology is reported. The importance of tube‐in‐tube CVD growth, which can significantly suppress the equilibrium shift to the decomposition direction and facilitate that to the synthesis reaction direction, for the synthesis of high‐quality Cr5 Te8 with accurate composition, is highlighted. By precisely adjusting the growth temperature, the thickness of Cr5 Te8 nanosheets is tuned from ≈1.2 nm to tens of nanometers, with the morphology changing from triangles to hexagons. Furthermore, magneto‐optical Kerr effect measurements reveal that the Cr5 Te8 nanosheet is ferromagnetic with strong out‐of‐plane spin polarization. The Curie temperature exhibits a monotonic increase from 100 to 160 K as the Cr5 Te8 thickness increases from 10 to 30 nm and no apparent variation in surface roughness or magnetic properties after months of exposure to air. This study provides a robust method for the controllable synthesis of high‐quality 2D ferromagnetic materials, which will facilitate research progress in spintronics. Abstract : 2D ferromagnetism Cr5 Te8 single crystals with high crystallinity are successfully synthesized via a tube‐in‐tube chemical vapor deposition growth. The as‐grown Cr5 Te8 nanosheet shows air‐stable and thickness‐tunable ferromagnetic properties with strong out‐of‐plane spin polarization, which open up new prospects for exploring 2D magnetism and spintronic device applications.